Optimizing Early-Stage Drug Discovery through Project Management: Evaluating the Strategic Value of Early Project Manager Assignments in the Pharmaceutical Sector - Sunkara, Sowmya; Desfriana Sari (Escalate : Economics and Business Journal, 2025)
The effectiveness of pharmaceutical research and development increasingly relies on aligning scientific innovation with structured operational management. This study examines the strategic impact of assigning project managers (PMs) during the early stages of drug discovery, particularly in the pre-lead optimization (pre-LO) phase. Employing a mixed-methods design that combines semi-structured interviews, document analysis, and quantitative surveys, the research compares key performance indicators between pre-LO and post-lead optimization (post-LO) teams. Quantitative and qualitative findings demonstrate that the absence of dedicated PMs in early discovery results in fragmented communication, unclear role expectations, and weak cross-functional coordination. In contrast, post-LO teams with PM involvement report higher levels of goal alignment, structured decision-making, and operational clarity. Statistical and thematic analyses reveal that PM competencies in communication, facilitation, and strategic alignment are more influential on project success than technical or scientific expertise. The study proposes a conceptual framework emphasizing the early integration of project management practices to enhance collaboration, mitigate risks, and streamline transitions from discovery to development. These insights offer both theoretical contributions to pharmaceutical project governance and practical recommendations for improving R&D productivity through early-phase project leadership.